2019
DOI: 10.1111/jfbc.12943
|View full text |Cite
|
Sign up to set email alerts
|

Starch composition, antioxidant potential, and glycemic indices of various varieties of Triticum aesitivum L. and Zea mays L. available in Pakistan

Abstract: Many varieties of Triticum aesitivum L. (Bread wheat) and Zea maize L. (maize) have been developed in Pakistan, which are randomly consumed by normal individuals and diabetic patients. In this study, 17 wheat and 9 maize varieties were tested for starch composition, glycemic index, radical scavenging activities, and lipid profile. Among various wheat samples, KPK15 was observed to have highest 2,2‐diphenyl‐1picrylhydrazyl radical scavenging activity, while CZP132011 was highest radical scavenger among various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(43 reference statements)
0
3
0
2
Order By: Relevance
“…The larger value of the correlation coefficient and lower RMSE indicates the high prediction accuracy and correlation between the actual value and the predicted value. 1 No feature reduction means that all the data features were used. 2 HCC represents the highest correlation coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger value of the correlation coefficient and lower RMSE indicates the high prediction accuracy and correlation between the actual value and the predicted value. 1 No feature reduction means that all the data features were used. 2 HCC represents the highest correlation coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…Sweet corn ( Zea mays L. saccharata ) is a vegetable crop with high nutritional and edible value as it is rich in sugar, various amino acids, vitamins, minerals, and dietary fiber [ 1 , 2 , 3 ]. Sweet corn has many varieties and they are favored by consumers all over the world, more so than common corn [ 1 ]. It has been reported that the planting area of sweet corn in China has gradually expanded in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diferindo-se, principalmente, pelos teores de açúcar e amido dos grãos (Bhatt et al, 2012). Conceituado uma hortaliça de alto valor nutricional e comestível, pois é rica em açúcar, diversos aminoácidos, vitaminas, minerais e fibra alimentar (Aziz et al, 2019;Yang et al, 2018).…”
Section: Introductionunclassified
“…A técnica NIR pode ser usada para analisar o conteúdo dos principais componentes das sementes de milho, como proteínas, amidos e lipídios (PENG et al, 2017). O milho doce possui um alto teor de açúcar solúvel, vários aminoácidos, vitaminas, minerais e fibras alimentares e menor teor de amido (AZIZ et al, 2019;YANG et al, 2018) = significativo e não significativo pelo teste F a 5% de probabilidade; F = valor de F calculado; CV = coeficiente de variação. Médias seguidas pela mesma letra, na coluna, não diferem entre si pelo teste de Tukey, a 5% de probabilidade.…”
Section: Espectroscopia No Infravermelho Próximo -Nirunclassified